A randomized open-label trial on the use of budesonide/formoterol (Symbicort®) as an alternative reliever medication for mild to moderate asthmatic attacks. - Chew, Keng Sheng; Kamarudin, Hamizah; Hashim, Che Wan (2012)
BACKGROUND